Making EM systems and bore logs speak the same language. Issue 1 (1st December 2019) - Davis, Aaron; Hauser, Juerg
Summary: Borehole induction logs, together with lithology records, are valuable for inferring geological and geophysical features in the subsurface. They offer insight in the relationship between geology and geophysics, and are an important source of information for determining the success of a planned airborne electromagnetic (AEM) survey for recovering features of interest. Often, bore logs are used as the 'ground-truth for an AEM system, and are employed for system selection pre-survey and 'validation' post-survey. We discuss the use of electromagnetic borehole logs for calibrating and validating AEM survey results in a sensible way: by comparing the measurements at the resolution power of the AEM system itself.